Electoral Justice in Indonesia's Presidential System: A Normative Study of the Presidential Threshold and Constitutional Court Decision No. 14/PUU-XI/2013 - Santoso Budi Nursal Umar; FX. Hastowo Broto Laksito; Lintang Cahya Primadani (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to normatively analyze the legal basis, rationality, and implications of the presidential threshold on the multi-party system and the principle of electoral justice in Indonesia, with a focus on Constitutional Court Decision Number 14/PUU-XI/2013. Thru a normative legal approach, this research examines the provisions of Article 222 of Law Number 7 of 2017 concerning General Elections and the Constitutional Court's constitutional arguments in maintaining the presidential nomination threshold. The analysis results show that although formally the presidential threshold is an open and legitimate legal policy, it substantially creates political inequality and limits the participation of small parties in the multi-party system. The Constitutional Court's decision is considered not fully reflective of the principles of electoral justice and popular sovereignty, as it prioritizes government stability over political equality. Therefore, it is necessary to reformulate the presidential candidacy threshold policy to make it more proportional, inclusive, and aligned with the principles of constitutional democracy. This reform is expected to strengthen the legitimacy of Indonesia's presidential system without neglecting the fundamental values of justice and political representation of the people.